The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12185-009-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin blocks cells survival signal pathways and induces apoptosis of HL-60 cells in vitro

Abstract: To investigate the anti-cancer effects and molecular mechanism of deguelin on the human leukemia HL-60 cells, to explore the expression and clinical significance of p-AKT, survivin and Bcl-2 in leukemia cell line HL-60 cell. Cell growth rate was assessed by MTT assay. Apoptotic index was evaluated by TUNEL staining. Apoptosis was detected by Annexin V-FITC Apoptosis Detection Kit and transmission electron microscopy (TEM), expression of p-Akt, Bcl-2 and surviving in HL-60 cells was checked by Western blot. Deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Previous reports have shown that deguelin inhibits the growth of cancer cells (18, 21, 22). In the present study, we evaluated whether deguelin could inhibit the metastasis of pancreatic cancer along with primary tumor growth.…”
Section: Resultsmentioning
confidence: 94%
“…Previous reports have shown that deguelin inhibits the growth of cancer cells (18, 21, 22). In the present study, we evaluated whether deguelin could inhibit the metastasis of pancreatic cancer along with primary tumor growth.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, deguelin was confirmed to have induced apoptosis by inhibiting PI3K activity and downregulating the pAkt-level, with no effects on MAPK pathways (10). Subsequent studies have demonstrated that deguelin induced apoptosis by inhibiting the PI3K/Akt pathway in human leukaemia HL-60, U937 and human breast cancer MCF-7 cells (11)(12)(13).…”
Section: Deguelin a Novel Anti-tumorigenic Agent Targeting Apoptosismentioning
confidence: 95%
“…Deguelin, a natural rotenoid isolated from Leguminosae plants like Mundulea sericea [ 15 ], has been shown to be effective in reducing the growth of several human tumor cell lines, both in vitro [ 16 , 17 ] and in tumor xenograft models such as breast or lung carcinomas [ 18 , 19 ]. Deguelin is a potent inhibitor of HSP90 [ 20 , 21 ] and mitochondrial bioenergetics [ 22 ], and decreases the activity of the AKT/NFκB pathway [ 23 ] leading to a reduced expression and function of several NFκB-regulated genes involved in cell survival and proliferation, such as BCL2, BCL-X L , XIAP, cIAP, survivin, CCND1 (cyclin D1), CCNE (cyclin E), or CDK4 [ 16 , 19 , 24 , 25 ]. Deguelin has been shown to promote apoptosis of CLL cells, promoting downregulation of IκBα [ 26 ].…”
Section: Introductionmentioning
confidence: 99%